The Relationship Between Foreign Producer Price İndex And Oil Prices: Toda-Yamamoto Causality Analysis Turkey Case (2010:01-2023:10) (Third Sector Social Economic Review, 2025)
Following the 1973 Arab-Israeli war, which marked the beginning of the oil crisis with global economic and political repercussions, the effects of the crisis on oil-dependent Turkey were analyzed.In addition to these analyses, the consequences of another possible oil crisis have also started to be investigated in the literature.This study analyses how the increase in oil prices affected the foreign producer price index in Turkey between 2010:01 and 2023:10. In the study, the causality relationship between changes in the prices of intermediate goods, durable and non-durable consumer goods, energy and capital goods and oil prices was tested.. The Fractional Frequency Fourier ADF unit root test and the Toda-Yamamoto causality test were applied in the study. As a result of the study, it is determined that there is a unidirectional causal relationship from oil prices to the determinants of the foreign producer price index, and suggestions are presented in the conclusion section. The fact that there is no study in this context and that both the data and the tests used are up-to-date suggests that the study will contribute to the literature.
Keywords: Foreign Producer Price Index; Oil Price; Turkey; Fractional Frequency Fourier ADF Unit Root Test; Fourier Toda-Yamamoto Causality Test